Right to Case Files in Criminal Cases in Indonesia - Rahim, Abdul; Rahim, Muhammad Ibnu Fajar (Manunggal Halim Jaya, 2023)
Indonesia, as a democratic country that prioritises human rights, pays special attention to the protection of the rights of its citizens involved in the criminal justice process. In this regard, case files are an important element in the preparation of evidence in criminal cases. However, there is a misalignment in the criminal law regarding how to access case files. Article 72 of KUHAP allows suspects to request a copy of the investigation report, while Article 143(4) of KUHAP requires the prosecutor to include the case file when submitting the case to the court. In order to ensure fairness in the criminal justice system and maintain cost-efficiency in the handling of cases, it is important to explore and clarify the right of access to case files. This paper aims to identify the ideal form of such a right in order to accommodate the needs of suspects, defendants or prisoners in properly preparing their defence in the Indonesian criminal justice process. In the Indonesian criminal justice system, case files are important documents used by suspects, defendants or prisoners to prepare a defence in a criminal case. Unfortunately, the right of access to case files, as stipulated in the Criminal Procedure Code (KUHAP), still creates confusion. Article 72 of the Criminal Procedure Code entitles the suspect to request a copy of the investigation report, while Article 143(4) of the Criminal Procedure Code requires the prosecutor to include the case file when submitting the case to the court. This paper concludes that Article 72 of the Criminal Procedure Code needs to be revised to clarify the right of access to case files. The revision proposes changing the text to read